2012
DOI: 10.1002/gea.21429
|View full text |Cite
|
Sign up to set email alerts
|

Multiproxy Analyses of Stratigraphy and Palaeoenvironment of the Late Palaeolithic Grabow Floodplain Site, Northern Germany

Abstract: Changing river courses and fluctuations of the water table were some of the most fundamental environmental changes that humans faced during the Late Glacial, particularly as these changes affected areas intensively used for settlement and resource exploitation. Unfortunately, only a few stratigraphies have been documented in the North European plain that show the interaction between river development, vegetation history, and occupation by Late Palaeolithic humans. Here, we present the results of detailed strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…1. (a) (Weber et al, 2010;Brock et al, 2011;Housley et al, 2012Housley et al, , 2013Housley et al, , 2014aTolksdorf et al, 2013;MacLeod et al, 2014;Tipping et al, 2014) this paper focuses on only the broad patterns.…”
Section: Cryptotephra Associated With Late Palaeolithic Sitesmentioning
confidence: 94%
“…1. (a) (Weber et al, 2010;Brock et al, 2011;Housley et al, 2012Housley et al, , 2013Housley et al, , 2014aTolksdorf et al, 2013;MacLeod et al, 2014;Tipping et al, 2014) this paper focuses on only the broad patterns.…”
Section: Cryptotephra Associated With Late Palaeolithic Sitesmentioning
confidence: 94%
“…As horizon markers, they capture snapshots in time and, equally as important, across space, thus theoretically solving many of the archaeological issues described above. Studies published by RESET members (Lowe et al, 2012;Housley et al, 2013;Tolksdorf et al, 2013) have demonstrated the utility of addressing cultural chronologies through the use of tephra identification and analysis. While they do have considerable potential, it is also important to keep in mind that tephras have limitations.…”
Section: The Utility Of Tephramentioning
confidence: 99%
“…To estimate the stratigraphical order of the channel generations, samples were taken from the basal lacustrine sediments of the channel fills for palynological investigations. The species composition was compared to records from the Jeetzel valley (Lesemann 1969, Christiansen 2008, Turner 2012, Turner et al 2013, Tolksdorf et al 2013b to estimate their biostratigraphical position. Based on these results, a palaeochannel with the onset of lacustrine sedimentation in the early Holocene was identified at the outskirts of the dune as potential archive for the reconstruction of the local vegetation development during the Holocene (Fig.…”
Section: Geology and Topographymentioning
confidence: 99%